Perovskites: Multiphoton Absorption and Applications. Issue 23 (8th May 2021) - Zhou, Feng; Ran, Xing; Fan, Dianyuan; Lu, Shunbin; Ji, Wei
Abstract: Recently, there have been intensive and extensive research works on perovskites because of their excellent electrical and optical properties. This review is focused on their multiphoton absorption (MPA) and applications. All the MPA coefficients or cross‐sections reported in the literature are summarized. Many experimental data show that the MPA strengths of nanoscale perovskites are several orders of magnitude greater than their bulk counterparts. The second‐ and third‐order quantum perturbation theories predict that, while the two‐band transitions play a significant role in 3D crystals of perovskites, the exciton‐light interactions dominate in the case of 2D perovskites. Other influencing factors on the MPA magnitudes are also discussed. Their potential applications are also highlighted in laser‐frequency upconversion and sub‐bandgap photodetection. Abstract : Intensive and extensive research works are summarized here to reveal the superior multiphoton absorption (MPA) properties of perovskites. The multiphoton absorption strengths of nanoscale perovskites are greater than their bulk counterparts due to many factors. Perovskites with efficient multiphoton absorption are of great potential for next‐generation technologies on laser‐frequency upconversion, sub‐bandgap photodetection, and bioimaging.